Impartiality of the Implora Lipstick Brand and its quality on Palangka Raya consumer loyalty - Cahyati, Etri; Sintani, Lelo; Karuehni, Ina (JSM: Jurnal Sains Manajemen, 2024)
This study aims to empirically explain the impact of brand image and product quality on customer loyalty towards Implora Lipstick Products in Palangka Raya. This study employs quantitative methodologies within a descriptive research framework. The sample size in this study consisted of 96 respondents. This study's primary and secondary data sources are primary and secondary data. The data analysis procedure employs validity and reliability assessments, classical assumption tests, multiple linear regression analysis, and hypothesis testing utilizing the SPSS version 26 software. The findings of this study suggest that (1) Brand Image has a partially significant impact on Customer Loyalty, (2) Product Quality has a partially significant impact on Customer Loyalty, and (3) Brand Image and Product Quality have a considerable simultaneous impact on Customer Loyalty